2009
DOI: 10.1177/0261018308101626
|View full text |Cite
|
Sign up to set email alerts
|

Social policies and refugee resettlement: Iraqis in Australia

Abstract: In this paper, we analyse national social policies that mediate the experiences of Iraqi refugees in Australia. Drawing on qualitative in-depth interviews conducted with this population in Melbourne, the capital of Victoria in Australia, and a small town in country Victoria, we delineate how social policies can lead to visible (formal) and invisible (informal) exclusion of refugees. We use two Australian policies; temporary protection and regional resettlement of refugees, to demonstrate how official Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…144 Johnson, Vasey, and Markovic, for example, found that Iraqi refugees living in a regional town in the state of Victoria had limited employment opportunities despite being professionally qualified, and participants commonly stated that the wages were poor and the type of work demeaning. 145 In addition, they found English skills difficult to obtain in their local area with English classes stopping altogether, and that access to services in the social and health sectors was limited. It is difficult to determine whether these problems were simply 'teething difficulties' due to the newness of the regional settlement initiative.…”
Section: Culture Shock (Intergenerational Disputes and Gender Role Ismentioning
confidence: 99%
“…144 Johnson, Vasey, and Markovic, for example, found that Iraqi refugees living in a regional town in the state of Victoria had limited employment opportunities despite being professionally qualified, and participants commonly stated that the wages were poor and the type of work demeaning. 145 In addition, they found English skills difficult to obtain in their local area with English classes stopping altogether, and that access to services in the social and health sectors was limited. It is difficult to determine whether these problems were simply 'teething difficulties' due to the newness of the regional settlement initiative.…”
Section: Culture Shock (Intergenerational Disputes and Gender Role Ismentioning
confidence: 99%
“…Australia grants around 13,750 humanitarian visas each year, 1 of which 6000 are for refugees resettled through the United Nations High Commissioner for Refugees (UNHCR) (Karlsen, 2015). Engaging in ‘burden sharing’ arguments, Australia has implemented a regional resettlement policy since 2004, whereby refugees with no family or social links in Australia are actively resettled to regional areas (Johnston et al, 2009) to alleviate labour shortages and foster integration through employment (Schech, 2014). However, this measure has at times been described as an attempt to ‘appease a fearful white electorate’ (Robinson, cited in Schech, 2014: 602) nervous about the development of racially segregated urban ‘ghettos’.…”
Section: Introductionmentioning
confidence: 99%
“…Most refugees represent vulnerable communities (Baker, Gentry, and Rittenburg 2005) and therefore need substantial assistance to integrate into their new host country's economic and social systems. This high level of vulnerability is why host countries, via United Nations conventions, continue to design integration programs to address gaps in education, social integration, employment, and health care (Johnston, Vasey, and Markovic 2009). Yet, while the primary objectives of such programs are to address refugees' needs to better integrate into host societies, not all refugees necessarily embrace the options provided, even when there is a demonstrable need (Peisker and Tilbury 2003).…”
mentioning
confidence: 99%